2019
DOI: 10.3892/mmr.2019.10510
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG6 inhibits cell proliferation and metastasis by targeting ETS1 via the PI3K/AKT/mTOR pathway in colorectal cancer

Abstract: The term 'long non-coding rnas' (lncrnas) refers to all non-protein coding transcripts >200 nucleotides in length. Dysregulation of lncRNAs has been identified in colorectal cancer, which is one of the more serious types of cancer worldwide, third place in the mortality rates, and is associated with poor prognoses. novel evidence suggests that lncrnas serve an important role in regulating the development and progression of colorectal cancer. in the present study, it was demonstrated that SnHG6 expression was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
(37 reference statements)
5
30
0
Order By: Relevance
“…However, the prognostic significance of SNHG6 in patients with NSCLC is unclear. Consistent with a previous study, we found that SNHG6 expression was increased and associated with poor prognosis, pathological stage and lymph node infiltration, acting as an independent prognostic factor of tumor recurrence in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the prognostic significance of SNHG6 in patients with NSCLC is unclear. Consistent with a previous study, we found that SNHG6 expression was increased and associated with poor prognosis, pathological stage and lymph node infiltration, acting as an independent prognostic factor of tumor recurrence in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have showed that SNHG6 can act as an oncogenic factor or a tumor suppressor in cancers . On the one hand, SNHG6 facilitates tumor cell progression by activating JNK or TGF‐β/Smad signaling, 8,10 and on the other it suppresses cell proliferation and metastasis by inactivation of the PI3K/AKT/mTOR signaling in CRC . In the present study, consistent with a previous report, we found that knockdown of SNHG6 suppressed cell proliferation and invasion in vitro and in vivo, but overexpressing SNHG6 reversed these effects.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, Yoon et al (2012) found that lincRNA p21 can directly inhibit the translation of Jun B and CTNNB1. lncRNA SNHG6 can regulate cell proliferation by participating in the translation and splicing of microRNAs (miRNAs) in cancer (Meng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%